Chinese Water Systems Volume 4: Applied Water Management in China - Dohmann, Max; Grambow, Martin; Song, Yonghui; Wermter, Paul (Terrestrial Environmental Sciences, 2022)
This open-access book addresses latest Sino-German results of the joint research efforts within Major Water Program of the Chinese Government supported by German research funding. The Major Water Program aims at the restoration of polluted water environments and sustainable management of water resources in China. The joint BMBF-CLIENT project SINOWATER deals with three most significant and strongest polluted Chinese waters, the river Liao and the Dian-lake as well as Tai-lake in the area of the metropolises Shenyang, Kunming and Suzhou, respectively. The project was conducted by the Research Institute for Water and Waste Management at RWTH Aachen (FiW) e.V., Bavarian State Ministry of the Environment and Consumer Protection, Technical University of Munich, RWTH Aachen University, German and Chinese companies (Martin Membrane Systems AG, Steinhardt GmbH Wassertechnik, GuHong, JT-elektronik, bluemetric, Huawang Water, EVU Group, Atemis GmbH, i+f process GmbH) in close cooperation with Chinese Academy of Environmental Sciences, Tongji University, and the Dianchi Lake Management Authorities. Overall, the joint Sino-German research project SINOWATER provided solutions for the improvement of the water quality in the mentioned water bodies as well as development and optimization of Good Water Governance. These objectives could be achieved through the implementation of innovative German water technologies and the optimization of water management elements in the fields of industrial and municipal wastewater treatment as well as river and shallow lake management.